The Influence of the Quantity of Magnetic Materials Extracted from Electronic Waste on The Modulus and Electromagnetic Parameters of Polypropylene Composites - Hunyek, Anuchit (Srinakharinwirot University Journal of Sciences and Technology, 2025)
This research investigated the influence of the quantity of magnetic materials on modulus and electromagnetic parameters. We ground transformer cores into powder in a ball mill. We analyzed the obtained powder using the X-ray diffraction technique, which revealed it to be iron oxide powder. We mixed the iron oxide powder with polypropylene at weights of 0, 5, 10, 15, 20, and 25 phr using an internal mixer. Control temperature, screw speed, and mixing time. Next, we used the two-roll mill to roll the material into sheets and cut test samples for each technique. Scanning electron microscopy (SEM) pictures revealed the spread of iron oxide powder in the polypropylene matrix. As the amount of iron oxide increased, the clusters got bigger. Dynamic mechanical properties tests showed that the iron oxide powder mixing increased the modulus of polypropylene at any temperature. The electromagnetic parameters, namely magnetization, permeability, and permittivity, vary linearly with the iron oxide content.